EDUKASI HOLISTIK PADA IBU POSTPARTUM TERHADAP PEMBERIAN ASI: Holistic Education Of Postpartum Women On Giving - Nurlina (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2023)
Introduction : Breast milk is the best food for infants because it contains many substances and protective factors that are impotant for the growth and development of infants so as to reduce infant morbidity and mortality. This contens is very complete and complex, there are hunderds of bioactive molecules that can protect babies from infectione and help in the formation of a strong immune system. Objective : This study aimsto determine whether there is an effect of holistic education on post partum mother on the success of breastfeeding at the Watampone Health Center. Research Methods : Based on the results of the research that researchers have done, the average value of knowledge in the interventioan group before being given education was 4,88, the lowest score was 3 and the highest score was 7 (total score 10), while the average score in the intervention group after education was 9.00. while the average value of knowledge in the pre test control group was 4,82, while the average value of knowledge in the post test control group was 6,29. This shows that there is an effect of providing education on changes in knowledge of post partum mothers in exclusive breastfeeding. Conclution : This study concludes that there is an increase in post pratum mother’s knowledge of exclusive breastfeeding at UPT Puskesmas Watampone after education.